Establishing quality indicators for neck dissection: Correlating the number of lymph nodes with oncologic outcomes (NRG Oncology RTOG 9501 and RTOG 0234). Issue 22 (15th July 2016) - Divi, Vasu; Harris, Jonathan; Harari, Paul M.; Cooper, Jay S.; McHugh, Jonathan; Bell, Diana; Sturgis, Erich M.; Cmelak, Anthony J.; Suntharalingam, Mohan; Raben, David; Kim, Harold; Spencer, Sharon A.; et al.
Abstract : BACKGROUND: Prospective quality metrics for neck dissection have not been established for patients with head and neck squamous cell carcinoma. The purpose of this study was to investigate the association between lymph node counts from neck dissection, local‐regional recurrence, and overall survival. METHODS: The number of lymph nodes counted from neck dissection in patients treated in 2 NRG Oncology trials (Radiation Therapy Oncology Group [RTOG] 9501 and RTOG 0234) was evaluated for its prognostic impact on overall survival with a multivariate Cox model adjusted for demographic, tumor, and lymph node data and stratified by the postoperative treatment group. RESULTS: Five hundred seventy‐two patients were analyzed at a median follow‐up of 8 years. Ninety‐eight percent of the patients were pathologically N+. The median numbers of lymph nodes recorded on the left and right sides were 24 and 25, respectively. The identification of fewer than 18 nodes was associated with worse overall survival in comparison with 18 or more nodes (hazard ratio [HR], 1.38; 95% confidence interval [CI], 1.09‐1.74; P  = .007). The difference appeared to be driven by local‐regional failure (HR, 1.46; 95% CI, 1.02‐2.08; P  = .04) but not by distant metastases (HR, 1.08; 95% CI, 0.77‐1.53; P  = .65). When the analysis was limited to NRG Oncology RTOG 0234 patients, adding the p16 status to the model did not affect the HR for dissected nodes, and the effect of nodes did not differ with the p16 status. CONCLUSIONS: The removal and identification of 18 or more lymph nodes was associated with improved overall survival and lower rates of local‐regional failure, and this should be further evaluated as a measure of quality in neck dissections for mucosal squamous cell carcinoma. Cancer 2016;122:3464–71 . © 2016 American Cancer Society . Abstract : The removal and evaluation of 18 or more lymph nodes is associated with improved overall survival for patients with node‐positive mucosal head and neck cancer. This threshold should be further evaluated as a potential measure of quality in neck dissections.